Exploring factors influencing university students' purchase of smartphones / Muhammad Nazmi Haqim Kamarulamirin ... [et al.] - Kamarulamirin, Muhammad Nazmi Haqim; Abdul Halim, Nur Qasfareeny; Ya'akop, Yasmin; Md Rodzi, Zahari (UiTM Cawangan Negeri Sembilan, 2021)
A smartphone is a must for everyone since it helps users to stay connected and engaged through online browsing, music listening, and social media. They can access email, engage in gaming, and work from any location. The market is flooded with smartphones from a variety of manufacturers. Buying a smartphone requires some considerations. Therefore, the purpose of this study is to determine the factors that influence university students' smartphone purchases. This section will detail the methods used, including the research instrument, the study's respondents, data collecting, and data analysis. We used Google Form online survey with a total of seven factors influencing university students' purchase of smartphones; (1) price, (2) camera, (3) storage, (4) screen display, (5) battery, (6) RAM and processor and (7) operating system. Data collected in Google Form was screened and transferred to SPSS version 26 for analysis. The descriptive statistics were used to attain the objective of this study. Following are the findings of this study, which is further divided into demographics of the respondents followed by the main objective of this study; exploring factors influencing university students' purchase of smartphones.